2012
DOI: 10.1371/journal.pone.0036632
|View full text |Cite
|
Sign up to set email alerts
|

Co-Stimulation of PAFR and CD36 Is Required for oxLDL-Induced Human Macrophages Activation

Abstract: The oxidative process of LDL particles generates molecules which are structurally similar to platelet-activating factor (PAF), and some effects of oxidized LDL (oxLDL) have been shown to be dependent on PAF receptor (PAFR) activation. In a previous study, we showed that PAFR is required for upregulation of CD36 and oxLDL uptake. In the present study we analyzed the molecular mechanisms activated by oxLDL in human macrophages and the contribution of PAFR to this response. Human adherent monocytes/macrophages we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 32 publications
2
33
3
Order By: Relevance
“…In fact, we have previously observed that in macrophages the PAFR activation by oxidized Low Density Lipoprotein (oxLDL) increased LPS-induced IL-10 production and phosphorylation of ERK1/2 and p38 [16,17]. In the present study, however, the blockage of PAFR by antagonist treatment reduced IL-10 production but did not affect MAPK kinases phosphorylation in DCs.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…In fact, we have previously observed that in macrophages the PAFR activation by oxidized Low Density Lipoprotein (oxLDL) increased LPS-induced IL-10 production and phosphorylation of ERK1/2 and p38 [16,17]. In the present study, however, the blockage of PAFR by antagonist treatment reduced IL-10 production but did not affect MAPK kinases phosphorylation in DCs.…”
Section: Discussioncontrasting
confidence: 77%
“…Molecular mechanisms underlying these effects involve the production of PAFR ligands and STAT3 activation. Moreover, these mechanisms are different from what we previously observed in macrophages, since they are independent on PGE 2 production, PPARγ, or NF-kB activation [7,16,17]. IL-10 is an anti-inflammatory cytokine produced by macrophages, DCs, and lymphocytes, and is able to regulate the activation of innate and adaptive immune responses.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…15 PAF or oxidized molecules with PAF-like activity generated during stress situations such as hypoxia can engage the PAFR, which activates intracellular signaling pathways that lead to transcription of pro-inflammatory genes. 16 Although PAF is involved in acute renal dysfunction 17 its role in renal fibrosis and in EMT is not completely known. One of the most used experimental model of CKD is the unilateral ureter obstruction (UUO) model.…”
mentioning
confidence: 99%
“…Here, we observe that the PAFR deficiency led to a decrease in Akt phosphorylation in the liver, an effect that is maximized in HFD. In previous publications, we showed that oxidized lipids induce Akt phosphorylation in macrophages in the absence of insulin and in a PAFR-dependent manner (40). PI3K/Akt pathway activation is associated with M2 macrophages polarization (41).…”
Section: Discussionmentioning
confidence: 80%